AN ANALYSIS OF UNSCHEDULE SHUTDOWN TOWARD ROTARY EQUIPMENT BLOWER ENGINE 18C3101-2 BY ROOT CAUSE ANALYSIS (RCA) METHOD (Case Study in PT. Petrokimia Gresik) - Yanuarsah, Rendra; Widyaningrum, Dzakiyah; Jufriyanto, Moh. (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
AbstactPT Petrokimia Gresik is a fertilizer manufacturer assigned by the Government to produce and distribute subsidized and non-subsidized fertilizers. The NPK 3 unit is the place where production be held. However, within March - June 2019 there was significant amount of decreasing fertilizer production caused by Rotary equipment malfunction. This occurrence caused unscheduled shutdown. PT Petrokimia Gresik experienced loss in many breakdown units. The objection of this study is to determine the factors causing the breakdown of 18C3101-2 blower engine in NPK 3 unit and to create the most effective solution to be applied while overcoming the 18C3101-2 blower engine breakdown in the NPK 3 unit. Problem of this study is what caused a breakdown of the 18C3101-2 blower engine in the NPK unit. This research applies the Root Cause Analysis (RCA) method. The result shows that using the Fishbone Diagram approach figuring out the main problem caused troubleshooting of 18C3101-2 blower engine due to a clogged spray nozzle, the main cause of a clogged spray nozzle was the initial setting of spray nozzle pipe installation inefficient. Keywords: Rotary equipment, unschedule shutdown, Root Cause Analysis (RCA).